Qualitative test for the presence of borax in cilok sold in several locations in Bondowoso sub-district - Putra, Mohammad Edwinsyah Yanuan; Kurniawati, Emi (UNIVERSITAS MUHAMMADIYAH MATARAM, 2023)
Cilok is a food product from West Java made from cassava flour, meat and spices. This product is very popular among the people of Bondowoso Subdistrict, Bondowoso Regency. Unfortunately, there are some cilok sellers who have indicated that they add borax in the processing process to extend the shelf life of the cilok. In fact, borax should not be consumed as it can be harmful to human health. This study aims to determine the presence of borax in cilok sold by vendors at various locations in the Bondowoso sub-district. This type of research is descriptive. The sampling technique used was cluster sampling. The samples used in the study were cilok sold by 4 cilok sellers at different locations in Bondowoso District, Bondowoso Regency. The data analysis technique used in this study was qualitative descriptive analysis. The results showed that all four cilok samples tested were negative for borax and therefore safe for consumption. This shows that cilok sellers are aware of good and safe food processing.